Nurses’ knowledge of palliative care - Gvozdanović, Zvjezdana (Array, 2019)
Introduction. Palliative care has evolved to identify the specific needs of patients with severe and incurable diseases. An estimated 46,000 patients in the Republic of Croatia require some form of palliative care. The aim of this study is to examine nurses’ knowledge of palliative care. Methods. A cross-sectional study included 198 nurses. The survey was conducted during March and April of 2017. As a survey instrument, a 2-part questionnaire was used. The first part dealt with sociodemographic data and the second part consisted of a standardized palliative care quiz for nursing (PCQN) questionnaire. Results. Respondents gave the most correct answers in the area of pain and other symptoms control. It was found that there was no significant difference in gender, age, or seniority in knowledge of palliative care. Respondents who received informal education showed better knowledge. Conclusion. From the study conducted, we can conclude that nurses have insufficient knowledge of palliative care.